Developing Mobile Learning Media in Teaching Passive Voice - Rohimah, Nadya Khansa; Mulyadi, Dodi; Budiastuti, Riana Eka (LPPM Universitas Pancasakti Tegal, 2021)
Mobile phones can be well integrated into English instruction as creative and innovative teaching media to increase students' interest and motivation. This study was carried out to discuss the development of Mobile Learning Media (MLM). The goal was to determine the design of mobile phones to be used as android-based mobile learning media and window learning media in the online learning process. It also analyzed the effectiveness of English learning using MLM. The study employed Sugiyono's Research and Development design, which included nine steps: potential and problems, data collection, product design, design validation by experts, product trial, revision of product I, usage trial, revision of product II, and final product. Questionnaires, tests, and learning media in the form of application package files as research instruments were used to collect the data. The collected data were analyzed using descriptive statistics and the independent sample T-test. The findings of this study were as follows: 1) the validation of experts' media and material was in the relevant interpretation of a valid product. 2) MLM product is simple and practical of data to use. 3) The mean of pre-test and post-test results in this class showed a high significance, indicating that the product of MLM is one of the learning media that is very effective to use in the learning process. Students' perception was well-established, with 73.3 percent agreeing to use MLM in mastering passive voice.